Prevalence of Strongyloides stercoralis in the immunocompetent and immunocompromised individuals in Iran: a systematic review and meta-analysis. (23rd July 2021) - Eslahi, Aida Vafae; Olfatifar, Meysam; Houshmand, Elham; Johkool, Morteza Ghanbari; Zibaei, Mohammad; Foroutan, Masoud; Hosseini, Hamid; Badri, Milad
Abstract: Strongyloidiasis is a neglected tropical disease mostly distributed in tropical and subtropical regions. The current study evaluated the prevalence of Strongyloides stercoralis in immunocompetent and immunodeficient patients in Iran. The available online literature published from June 1994 to October 2020 was obtained from multiple English databases (PubMed, Science Direct, Scopus, Web of Science and Google Scholar) and four Persian databases (Magiran, Iran Medex, Iran Doc and SID). All statistical analyses were performed using R software (version 3.6) meta-package and p-values <0.05 were considered significant. From 1051 articles, 74 studies (248 656 individuals) met the inclusion criteria. The pooled prevalence of S. stercoralis was 2% (95% confidence interval [CI] 1 to 3) and 4% (95% CI 1 to 8) in immunocompetent and immunodeficient patients, respectively. In immunodeficient cases, the pooled prevalence of studies utilizing serology, culture and microscopic methods was 10% (95% CI 2 to 23), 1% (95% CI 0 to 6) and 1% (95% CI 0 to 1), respectively. In immunocompetent cases, the pooled prevalence of studies utilizing microscopic, culture and molecular methods was 2% (95% CI 1 to 3), 2% (95% CI 1 to 4) and 2% (95% CI 0 to 6), respectively. We propose an appropriate screening and control program along with comprehensive research regarding the frequency of strongyloidiasis in the country.